Die Entstehung komplexer Siedlungen im Zentraloman Archäologische Untersuchungen zur Siedlungsgeschichte von Al-Khashbah - Schmidt, Conrad 1976-; Döpper, Stephanie 1986-; Kluge, Jonas (Archaeopress Publishing, 2021)
Die Entstehung komplexer Siedlungen im Zentraloman: Archäologische Untersuchungen zur Siedlungsgeschichte von Al-Khashbah' presents the results of a survey conducted in 2015 and beyond by the Institut für die Kulturen des Alten Orients of the Universität Tübingen in Al-Khashbah, one of the largest Early Bronze Age sites on the Omani Peninsula. Ten monumental buildings, 273 tombs and other structures from the Hafit (3100-2700 BC) and Umm an-Nar periods (2700-2000 BC) were documented here. This makes Al-Khashbah ideally suited for the investigation of the beginnings of complex settlements and social structures in northern Inner Oman at the transition from the 4th to the 3rd millennium BC, because many of the achievements previously attributed to the Umm an-Nar period, such as monumental architecture and the smelting of copper, can already be proven here in the preceding Hafit period. In the Umm an-Nar period, the development of Al-Khashbah continues steadily, giving the site additional importance. According to the results of the survey, however, copper production at the site no longer seems to play a role in this period.00Aus den auf die frühe Bronzezeit folgenden Epochen des 2. und 1. Jahrtausends v. Chr. sowie des 1. und 2. Jahrtausends n. Chr. gibt es in Al-Khashbah nur äußerst wenige Befunde. Erst im 18.?20. Jahrhundert n. Chr. erfährt der Ort eine intensive Wiederbelebung, wovon insbesondere die alte Lehmziegelsiedlung im Norden der Palmenoase, eine kleine Siedlung im Osten des Untersuchungsgebiets, eine Reihe von Bewässerungsanlagen, mehrere Friedhöfe, Petroglyphen sowie zahlreiche an der Oberfläche gefundene spätislamische Keramikscherben zeugen
Keywords: Geschichte; Siedlungsarchäologie; al- Khashbah; Excavations (Archaeology) / Oman; Al-Khashbah (Extinct city); Oman / Antiquities; Fouilles (Archéologie) / Oman; Antiquities; Excavations (Archaeology); Oman; Al-Khasbah; Aufgabensammlung